The Everlasting Gospel : The Significance of Eschatology in the Development of Pentecostal Thought - Faupel, William D, (Journal of Pentecostal Theology Supplement Series, 2010)
How did Pentecostalism become the fastest growing movement within Christendom in the twentieth century? Faupel contends that Pentecostalism was propelled onto the world stage when early adherents felt commissioned by God to announce that Christ would soon return to establish his kingdom on earth. The gift of tongues would equip them supernaturally to proclaim this message to the nations in the language of the people. Although this expectation was soon disproved, the eschatological hope nevertheless remained the motivating force for Pentecostalism's rapid growth. This book has been prescribed reading on the Pentecostal hope for many years. This edition makes it available once again to a worldwide readership.